Low-Profile Induced-Voltage Distance Ranger for Smart Contact Lenses - Ghosh, Chayanjit; Mastrangelo, Alex; Karkhanis, Mohit; Deshpande, Adwait; Banerjee, Aishwaryadev; Kim, Hanseup; Mastrangelo, Carlos H. (IEEE transactions on biomedical engineering, 2021)
Objective: In this paper, we present a novel, low-profile, scleral-coil based, distance ranging system which is suitable for smart, accommodating contact lenses. Methods: We measure the induced emf between a set of four thin semi-circular coils patterned on flexible Kapton substrates that conform to the eyes' sclera. This induced emf is a function of eye gaze angles. The system then determines the distance from the eyes to the desired object via the triangulation of these eye gaze angles Results : Experiments on eyeball simulated tissue gels indicate an accurate prediction of object distance in the 0.1-15 D range with a 0.15 D RMS error and object direction in the −15 to 15-degree arc with 0.4-degree RMS error, respectively. The energy required was determined to be as low as 20 μJ per range reading. Conclusion: Experimental data shows that our proposed new method of eye-tracking and distance ranging system can accurately predict eye-gaze angles and object-distance, whilst using only 20 μJ per range reading. Significance: The high-accuracy, low-profile and reduced energy requirements of the proposed eye-tracking technique, make it suitable for applications in the vast field of adaptive optics such as smart contact lenses and other low-power vision corrective applications.